A Novel Bioresorbable Implant for Repair of Orbital Floor Fractures. (August 2015) - Teo, Livia; Teoh, Swee Hin; Liu, Yuchun; Lim, Laurence; Tan, Bernard; Schantz, Jan-Thorsten; Seah, Lay Leng
Abstract Purpose: To describe clinical, radiologic, and safety outcomes of orbital floor fracture repair using a novel bioresorbable polycaprolactone (PCL) mesh implant (Osteomesh™, Osteopore International, Singapore). Methods: This is a prospective interventional case series of orbital floor fractures repaired using a novel PCL mesh implant. Clinical evaluation was conducted at presentation and postoperatively at 1, 4, 12, 24 and 48 weeks. Computed tomography (CT) of the orbits was performed 1 year postoperatively. Results: A total of 20 patients were recruited. Mean follow up was 50.4 ± 31.88 weeks. The majority of the patients were male (60%) and of Chinese ethnicity (75%), and the mean age was 39.35 (range 13–69) years. The most common mechanism of injury was assault. The average fracture size was 21.9 mm (range 12–32 mm) in the anteroposterior meridian and 18.65 mm (range 6–27 mm) in the horizontal meridian. Fifty percent of the patients were classified as having a large orbital defect (horizontal width ≥20 mm). The binocular single vision (BSV) score improved from 72.1% preoperatively to 90.8% postoperatively (P < 0.05) for 17 patients who had pre and postoperative charts. BSV improvement did not differ significantly between those with large and small orbital fracture sizes. There were features of neobone formation on CT scan performed 1.5 years after implantation. Conclusion: This bioresorbable implant is a promising material for the repair of both small and large orbital floor fractures, giving good functional and aesthetic outcomes.